Analisis Kinerja Keuangan Perusahaan Dengan Metode Economic Value Added (EVA) Dan Financial Value Added (FVA) Pada PT. Indosat Tbk - Rizky Adhinugroho; Nor Norisanti; Faizal Mulia Z (Journal of Economic, Bussines and Accounting (COSTING), 2022)
PT Indonesian Satellite Corporation Tbk is an international telecommunication service provider in Indonesia. PT Indosat as a company that has provided and serves a very strong and storied development. Together become the largest telecommunication andmultimedia company in Indonesia for cellular services (Satelindo, IM3, StarOne). Each company has a financial statement in each period, if you want to assess whether the company is healthy or can not be seen from the company's financial performance in each period. One of them can use the method of Economic Value Added (EVA) and Financial Value Added (FVA). The purpose of this study to determine the effect of the company's performance on Indosat, using EVA and FVA method, in order to determine whether or not the added value of the company PT. Indosat Tbk. The method used in this research is Descriptive with methods that can be analyzed financial data at PT Indosat company from 2012-2016. The results of this study indicate that the added value of PT. Indosat Tbk in 2012 and 2016 and there is no added value in 2013-2015 using EVA analysis method. Then the analysis using the FVA method of value added in 2012-2016 which means showing the value added financial for the company or net profit of the company and depreciation able to cover equivalent depreciation. Keyword : Financial Performance, EVA, FVA